2012
DOI: 10.1186/1471-244x-12-178
|View full text |Cite
|
Sign up to set email alerts
|

What are the effects of having an illness or injury whilst deployed on post deployment mental health? A population based record linkage study of UK Army personnel who have served in Iraq or Afghanistan

Abstract: BackgroundThe negative impact of sustaining an injury on a military deployment on subsequent mental health is well-documented, however, the relationship between having an illness on a military operation and subsequent mental health is unknown.MethodsPopulation based study, linking routinely collected data of attendances at emergency departments in military hospitals in Iraq and Afghanistan [Operational Emergency Department Attendance Register (OpEDAR)], with data on 3896 UK Army personnel who participated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The TMHED adjusted OR was higher than that of Forbes et al. (; OR = 1.54) for postdeployment mental health problems among United Kingdom Army personnel who had any type of illness/injury while deployed. These rates are consistent with available evidence that health problems during deployment are associated with a higher risk of postdeployment mental health problems, but the effect was particularly pronounced for mental disorders in this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The TMHED adjusted OR was higher than that of Forbes et al. (; OR = 1.54) for postdeployment mental health problems among United Kingdom Army personnel who had any type of illness/injury while deployed. These rates are consistent with available evidence that health problems during deployment are associated with a higher risk of postdeployment mental health problems, but the effect was particularly pronounced for mental disorders in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Still, some personnel are at higher risk for postdeployment adjustment problems than others. A recent study showed that rates of postdeployment mental problems were higher for personnel who were injured or ill while deployed than for those who remained healthy (Forbes et al, 2012). Given that illness and injury are associated with increased risk of postdeployment mental disorders (DiMatteo, 2004;Koren, Norman, Cohen, Berman, & Klein, 2005), an increased risk also seems likely among personnel treated in theater for mental health problems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences of injuries are pertinent for military personnel, and for their families who frequently provide informal care during the recuperation process 1 2. The healthy partner often assumes the role of primary caregiver and takes on greater responsibility for household tasks, and for maintaining personal and social relationships, and social networks as seen in a study of wounded, injured or sick (WIS) US military personnel 3.…”
Section: Introductionmentioning
confidence: 99%
“…The high rates of post-traumatic stress disorder (PTSD) found by Forbes et al [1] in personnel medically evacuated from Iran and Afghanistan while on deployment is surprising. Those military personnel who were medically ill had similar rates of PTSD as those evacuated for injuries sustained in combat.…”
Section: Introductionmentioning
confidence: 99%